A Vertical PN Diode Constructed of MoS2/CsPbBr3 Heterostructure for High‐Performance Optoelectronics. Issue 3 (5th December 2021) - Xu, Jiao; Li, Jing; Wang, Hengshan; He, Chengyu; Li, Jianliang; Bao, Yanan; Tang, Huayi; Luo, Huaidong; Liu, Xiaochi; Yang, Yiming
Abstract: To boost the performance of perovskite‐based optoelectronic devices, 2D materials, which have high carrier mobilities and diverse band structures, are preferably chosen to integrate with perovskites. Up to now, 2D materials/perovskites heterostructured photodetectors are commonly based on parallel or lateral heterojunction. The former usually confronts the problem of large dark current, and the latter's optoelectronic performance is hard to be further improved, limited to the large resistance of perovskites. Here, a vertical PN diode, based on MoS2 /CsPbBr3 heterostructure, is demonstrated, where the CsPbBr3 is sandwiched by MoS2 and bottom Au electrode, and carriers' transit distance in CsPbBr3 is hence shortened to flake's thickness. Due to appropriate band alignment between MoS2 and CsPbBr3, efficient carriers' separation and transfer at junction area are confirmed by scanning photocurrent microscopy. The influence of thickness of MoS2 and CsPbBr3 on light absorption is simulated with finite‐difference time‐domain method. The vertical PN diode shows remarkable optoelectronic figures‐of‐merit, including large photoresponsivity (1.51 A W −1 ), low dark current (≈ 10 −13 A), and fast response (34/39 mS). In addition, when operated at V D = 0 V, the device still exhibits distinct power‐dependent response, indicating its potentiality for self‐powered photodetection. Abstract : A vertical PN diode, based on MoS2 /CsPbBr3 heterostructure, is proposed and studied. Scanning photocurrent microscopy is utilized to characterize photoinduced carriers' transport and band alignment in the heterostructure. Light absorption in the heterostructure is simulated with finite‐difference time‐domain, to estimate the flakes' thickness influence. Optoelectronic performance of the PN diode is tested and compared at different biases.